THE INTENTION TO ADOPTING CRYPTOCURRENCY OF JAKARTA COMMUNITY - Zamzami, Annisa Hakim (Dinasti Publisher, 2020)
The development of information technology encourages technological growth in the financial sector, namely cryptocurrency. Cryptocurrencies created by private parties still have many shortcomings in terms of security. So it needs an important role from the competent institution. In addition, during the Covid 19 pandemic, cash was considered a medium for spreading the virus. So one of the reasons China started releasing its own digital money was under the strict control of the People's Bank of China. Indonesia is the country with the highest number of positive indications for Covid-19 in Southeast Asia, especially in Jakarta. Therefore, this study examines the planning behavior of the people of DKI Jakarta to adopt cryptocurrency as a transaction tool, using the theory of planning behavior (TPB). 207 research samples were analyzed using covariance-based SEM method with the SmartPLS 2.0 tool. The results showed that only attitudes significantly affect individual intentions to use digital money. Meanwhile, subjective norms and behavioral control do not significantly affect individual intentions to adopt cryptocurrency